Assessing Quality Through Use: A Usability-Based Evaluation of the Conta gov.br Authentication Platform - Jubé, Demétrius de Almeida; Leite, Letícia Lopes (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
This article presents an empirical study that evaluated the Conta gov.br authentication platform, a nationally adopted service in Brazil, focusing on usability as a dimension of software quality. Thirty participants took part in usability testing using standardized metrics: System Usability Scale (SUS), Single Ease Question (SEQ), and Task Completion Time (TCT). Results showed variations in perceived usability influenced by demographic factors such as age and education level. Statistical correlations between scores and user profiles were also analyzed. Based on the findings, a Practical Guide was developed to support public institutions in their adoption strategies. The results contribute evidence-based insights to inform quality-oriented decisions in digital public services.